2004
DOI: 10.1521/jscp.23.1.61.26990
|View full text |Cite
|
Sign up to set email alerts
|

Can Self-Determination Help Protect Women Against Sociocultural Influences About Body Image and Reduce Their Risk of Experiencing Bulimic Symptoms

Abstract: According to the sociocultural approach of eating pathology, the more women perceive sociocultural pressures about body image, the more they endorse society's beliefs related to thinness and obesity which in turn, is associated with greater body dissatisfaction. Also, the more dissatisfied women are about their body image, the more they report bulimic symptoms. In the present study, the same sequence of variables was tested with the addition of a Global Self-Determination variable to examine why sociocultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 43 publications
10
58
1
6
Order By: Relevance
“…These hypotheses have already been tested and supported in one study. Pelletier, Dion, and Lévesque (2004) first tested a model that supported the sociocultural pathway to bulimia, observing that greater perceptions of sociocultural pressures about body image predicted greater endorsement of societal beliefs related to thinness and obesity, which, in turn, was associated with greater body dissatisfaction resulting in more bulimic symptoms. However, when general self-determination was added to the model, the results provided support for a protective role for self-determination.…”
Section: General Self-determination As a Protector Against Sociocultumentioning
confidence: 99%
See 2 more Smart Citations
“…These hypotheses have already been tested and supported in one study. Pelletier, Dion, and Lévesque (2004) first tested a model that supported the sociocultural pathway to bulimia, observing that greater perceptions of sociocultural pressures about body image predicted greater endorsement of societal beliefs related to thinness and obesity, which, in turn, was associated with greater body dissatisfaction resulting in more bulimic symptoms. However, when general self-determination was added to the model, the results provided support for a protective role for self-determination.…”
Section: General Self-determination As a Protector Against Sociocultumentioning
confidence: 99%
“…First, self-determination toward one's life in general should play two roles: one as a protective factor against sociocultural pressures about body image (Pelletier, Dion, & Lévesque, 2004), and the other as a significant determinant of the motivation toward eating behaviors (Pelletier, Dion, Slovinec-D'Angelo, & Reid, 2004). Second, specific self-determination for the regulation of eating behaviors should be an important predictor of both healthy eating and problem eating.…”
Section: Self-determined Motivation and Nonself-determined Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a culture that emphasizes thinness and weight control, preoccupation about weight may be related to dissatisfaction with one's body weight and shape as well as an overconcern about reaching an ideal weight. 3 This is particularly observed in women compared to men who appear to be much more comfortable with their weight. 4 A study performed in Canadian women having a body mass index (BMI) within acceptable limits (acceptable BMI defined as being between 20 and 24 kg/m 2 for the purpose of that study), showed that the proportion of those who desire to lose weight was quite elevated with 35% considering themselves above their desired weight.…”
Section: Introductionmentioning
confidence: 99%
“…For example, women's level of autonomy in their lives appears to protect against body image pressures (Pelletier & Dion, 2007) and is negatively associated with bulimic behaviours (Pelletier, Dion, & Lévesque, 2004). Further, in a sample of (mainly female) aerobics instructors, general autonomy need satisfaction was found to negatively predict body image concerns (i.e., body dissatisfaction and drive for thinness; Thøgersen-Ntoumani & Ntoumanis, 2007).…”
mentioning
confidence: 97%